PELAKSANAAN PEMBELAJARAN SENI BUDAYA (MUSIK) DI SMP NEGERI 22 PADANG - Fitri, Hayatul; Lumbantoruan, Jagar (SENDRATASIK UNP, 2019)
AbstractÂ This article aims to provide an overview of how to study the Art of Culture (music) di SMPN 22 Padang. This type of research is qualitative using a descriptive approach to analysis. The main instrument of this research is its own researchers and assisted with supporting instruments such as stationary, tape recorders and cameras. Data collection techniques are done by studying the library of interviews and observations. The steps for analyzing data are collecting data, identifying data, classifying data, describing and analyzing data. The results showed that the learning planning made by the teacher was less relevant because the topic of the lesson in K13 semester II was to play music ensembles of similar (local area/archipelago). Due to the inconsistency of the lesson topics in K13 resulted in KD and the KD indicator also not in accordance with the expected learning objectives K13. In formulating learning objectives does not contain cognitive, affective, and psychomotor domains. The Media used is not utilized to the fullest. Of all the problems on the afterlife performance teachers in carrying out the learning becomes less adequate and finally the learning becomes less effective.Â Keywords: implementation, cultural arts Learning (music)